Protection of Critical Infrastructures for Energy Supply (Academic Journal of Internal Affairs, 2020)
Continuous economic and social development is a defining feature of human history. Technological revolutions have been following each other at an ever-accelerating pace since the Industrial Revolution. As a result of this development, our ever-expanding supply of equipment results in a strong increase in energy demand. The comfort of mankind is provided by the ever-widespread electrification, that is, we are encountering electricity-based technologies in more and more areas of our daily lives. In addition to providing convenience, automation and the advancement of digital technologies improve the efficiency of economic activities and promote sustainable energy production. The life of an urbanized man is moving towards full automation. Smart homes, internet-based work and commerce are gaining ground. Self-learning software, thinking computers are spreading. Self-propelled vehicles run a test run. Without the continuous, reliable availability of electricity today's advanced technologies are worthless. Without electricity life stops. Based on this recognition, energy systems’ infrastructures are increasingly exposed to external attack. In addition to the reliability of technologies that play a decisive role in the supply of energy, it is necessary to take effective action against potential threats from the environment. This article, along with a description of power supply systems, identifies potential external threats and remedies available.
Keywords: energy; sustainable development; energy supply; security; infrastructure